Time in e-Learning Research: A Qualitative Review of the Empirical Consideration of Time in Research into e-Learning. (23rd January 2012) - Barbera, Elena; Clarà, Marc
Abstract : Time has been argued by several influential approaches as essential for understanding learning and teaching processes. In e-learning, however, the traditional time limits of such processes are modified, which implies challenges and possibilities for e-learning research. This paper is aimed at understanding how time is included in empirical e-learning research literature. With this aim in mind, the paper presents a qualitative review of 24 e-learning papers. Five issues are analysed: the conception of time, its inclusion in an explicative model, its inclusion in the research process, the analytical units, and the data used in the study of time. Based on our analysis, we discuss some implications and potentialities for e-learning research on the relations between time and learning.